MBTI Analysis of Technical Translators in Kazakhstan: Personality Insights - Em, Tatyana; Kalizhanova, Anna; Markus, Danil E. (International Journal of Language and Literary Studies, 2023)
This study introduces a novel approach for training technical translators and interpreters in Kazakhstan using international best practices. The Myers-Briggs Type Indicator (MBTI), widely used globally but barely known in Kazakhstan, assesses individuals’ decision-making, perception, and interaction styles relevant for translators. Twelve technical translators and five specialists were surveyed. Semi-structured interviews, code extraction, and descriptive analysis examined participants’ personality profiles. Results indicated translators with intuitive-logical personalities (NT) outperformed sensory-logical ones (ST), although the latter succeeded given multimodal materials and professional networks. Communicating with coworkers proved challenging for NT and NF types; the former needs skill development and the latter career support. Effective technical translation and interpretation without technical knowledge requires strong communication, proximity to facilities, intuitive-logical reasoning, and experience.